EFFECTIVENESS OF VENTILATION CARBON FILTER IN CONTROLLING MICROORGANISMS IN ROOM AIR - Jessy Novita Sari; Gustomo Yamistada (Pusat Riset dan Inovasi Nasional, 2023)
The house is a place of residence or shelter for individuals or groups. In general, the house has ventilation, ventilation functions as a rotation or exchange of air in the room. The existence of ventilation is very important for air exchange, but the existing air pollution, including microbes, causes air exchange through ventilation into the house which is not safe for health. So there is a need for filtration so that the polluted air can be filtered. . The purpose of this study was to determine the effectiveness of the use of ventilation carbon filters in controlling microorganisms in room air.This type of research is experimental research with a research design using the Pre and Post Test Only Design .The results showed 1) There was an average decrease in the number of germs in the room by 1412 CFU/m3 or 62%. 2) There is an average decrease in the number of fungi in the room by 17 CFU/m3 or 44%. 3) there is a significant difference in reducing the number of germs in the room air before and after being given a carbon filter ventilation with p-Value = 0.000. 4) There is a significant difference in the reduction of mold numbers in room air before and after being given a carbon filter ventilation p-Value = 0.035. The recommendations given are that it is hoped that the community can use carbon filters as adsorbents for air pollutants that enter the room. Carbon filter ventilation that has been used needs to be washed and activated so that it can adsorb air pollutants more optimally. The room still has to be cleaned regularly to reduce air pollution which poses a risk to the health of occupants.